Landscape Plant Management in Pinge Tourism Village - Ida Bagus Komang Mahardika; Siti Maslizah Abdul Rahman; Ketut Agung Sudewa; I Gusti Bagus Udayana; Desak Ketut Tristiana Sukamadewi; Ni Komang Alit Astiari; A. A. S. P. R. Andriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Tourist villages will need infrastructure that supports tourism activities such as places to eat, places to stay, rest areas, galleries, and so on, one of whose goals is to improve the living standards of local people. This causes the number of plant species to decrease. Plant conservation by utilizing local wisdom is one of the efforts to reduce the decline in the number of plant species. Balinese people need many types of plants to support their ceremonial activities. The application of Tri Hita Karana and Tri Mandala in the daily life of the Balinese people is expected to support plant conservation activities and support tourism activities and provide economic benefits in the Pinge traditional village. The concept of Tri Hita Karana derives from the concept of Tri Mandala which consists of the main mandala as a parahyangan or holy place, Madya mandala in the form of a yard which includes residential buildings and natah, while nista mandala yard in the form of the back house (teba) and the yard of the front house (telajakan). Traditional Balinese gardening uses the concept of Tri Mandala. The problems raised in this "community service program" are still unorganized placement of plants in the Tri Mandala area and the lack of availability of plants for landscape management following the Tri Hita Karana concept. To support the management of landscape plants following the tri hita karana concept, Warmadewa University in collaboration with the Unda Anyar Seedling Nursery Center, Ministry of Environment and Forestry (KLHK) assisted plant seeds in the form of Cempaka seeds, avocados, sandalwood, majegau, jackfruit, rejasa, sawo, and soursop. Conducting webinars on the topic of landscape plant management following the tri hita karana concept. Inviting the people of Pinge Village to actively participate in planting Tri Mandala following the concept of Tri Hita Karana.